Observation of dark and bright pulses in q-switched erbium doped fiber laser using graphene nano-platelets as saturable absorber - Nur Hidayah Muhamad Apandi; Siti Nur Fatin Zuikafly; Nabilah Kasim; Mohd Ambri Mohamed; Sulaiman Wadi Harun; Fauzan Ahmad (Bulletin of Electrical Engineering and Informatics, 2019)
In this paper, a passively Q-switched Erbium doped fiber laser (EDFL) by residing Graphene nanoplatelets (GnPs) embedded in polyvinyl alcohol (PVA) based saturable absorber (SA) is demonstrated. To aid the dispersion of GNPs, a surfactant is used and then it is mixed with polyvinyl alcohol (PVA) as host polymer to develop GnPs-PVA film based passive SA. The GnPs-PVA based film then integrated in laser cavity in ring cavity configuration for pulse laser generation. The experimental works show that the proposed passive SA operates at input pump power range from 77 mW to 128 mW with a tunable repetition rate from 78.4 kHz to 114.8 kHz and a shortest pulse width of 3.69 µs. The laser produces maximum instantaneous output peak power and pulse energy of 7.3 mW and 30.46 nJ, respectively and accompanied by signal to noise ratio (SNR) of 64 dB.